Analisis Kesalahan Berbahasa pada Tataran Semantik Melalui Produk Iklan Kemasan - Mayang Sari; Casim Casim (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This research aims to explain the symptoms of language errors, especially ambiguity at the semantic level in packaged advertising products. Ambiguity is a form of duplicity that can confuse listeners, making the message conveyed by the speaker difficult to understand. Advertising, as a communication and information medium, uses spoken and written language to convey messages or opinions. The advertisements analyzed in this research include advertisements for medicines, drinks and food. This research uses a descriptive qualitative method, by producing descriptive data in the form of written words on packaging advertisements. The research subjects were packaged advertising products which were analyzed using data collection techniques in the form of reading and taking notes on the advertisements obtained. It is hoped that the results of this research will provide an overview of the potential for language errors in packaging advertising which can cause ambiguity or confusion for consumers. This research also aims to analyze how ambiguity in advertising language can influence consumer perceptions and explain the implications of these language errors on the effectiveness of advertising in attracting attention and influencing consumer purchasing decisions.